2022
DOI: 10.1002/ar.25040
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between compensatory hyperplasia of the myodural bridge complex and reduced compliance of the various structures within the cranio‐cervical junction

Abstract: The myodural bridge complex (MDBC) is described as a functional anatomic structure that involves the dense connective tissue fibers, muscles, and ligaments in the suboccipital region. It has recently been proposed that the MDBC can influence cerebrospinal fluid (CSF) circulation. In the present study, bleomycin (BLM), a type of antibiotic that is poisonous to cells, was injected into the posterior atlanto-occipital interspace (PAOiS) of rats to induce fibrous hyperplasia of structures in PAOiS. Sagittal sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…It has been reported in our previous study that hyperplastic changes of the MDBC in this model resulted in increased stiffness of the SDM and reduced compliance of various structures within the cranio-cervical junction 21 . In a hypothesis study about the pathophysiology of symptomatic adult Chiari malformation Type I, it was mentioned that the stiff dura may limit the natural expansion of the subarachnoid space, thereby changing the pressure environment of CSF flow 22 .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It has been reported in our previous study that hyperplastic changes of the MDBC in this model resulted in increased stiffness of the SDM and reduced compliance of various structures within the cranio-cervical junction 21 . In a hypothesis study about the pathophysiology of symptomatic adult Chiari malformation Type I, it was mentioned that the stiff dura may limit the natural expansion of the subarachnoid space, thereby changing the pressure environment of CSF flow 22 .…”
Section: Discussionsupporting
confidence: 49%
“…In our previous animal study, according to the fibrogenic effect of bleomycin, we found that injection of bleomycin into the posterior atlanto-occipital interspace of rats led to proliferative changes in the MDBC fibers and an increased sectional area of the RCDmi, as demonstrated by histological and semi-quantitative studies 21 . Thus, the same methods were used in the present study and yielded consistent results.…”
Section: Discussionmentioning
confidence: 69%
“…In these experiments, surgical disruption of the myodural bridge increased the bulk flow of CSF out of the spinal compartment (presumably by dilating the rostral portion of the spinal dura) and increased the propagation time of the secondary pulsations (presumably by creating localized turbulence at the foramen magnum). A recent contribution [35] examined how pathological conditions within the myodural bridge could alter compliance of structures around the foramen magnum in mice. Our conclusion is similar, but we would argue that the relationship between the myodural bridge, dural compliance, and CSF pressure is a regular part of the CSF dynamics influencing the flow and pressure of the CSF in both the healthy and pathological states.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] Some scholars thought that MDBC could modulate the compliance of SDM. [ 35 , 36 ] The SDM is attached to the periphery of the foramen magnum and the internal aspects of the posterior C1 and C2 vertebral bodies, and to the coccyx through the filum terminale. The SDM also invests on the spinal nerve roots as far as the level of the intervertebral foramen.…”
Section: Discussionmentioning
confidence: 99%